Follicular dendritic cell sarcoma: a report of cases and a literature review - S. B. Alieva; I. A. Zaderenko; A. M. Mudunov; A. V. Nazarenko; V. V. Mochal’nikova; O. N. Karp; R. I. Azizyan; A. A. Akhundov; V. Т. Aslanukov; O. P. Trofimova; A. V. Khromushina; A. E. Каzimov (Опухоли головы и шеи)
The article is devoted to the diagnosis and treatment of an extremely rare tumor – a sarcoma from follicular dendritic cells with extranodal lesion in the region of the head and neck. These tumors are characterized by a high potential for metastasis and recurrence. Difficulties in choosing the optimal treatment tactics are associated with a small number of observations. Surgical, radiotherapeutics and chemotherapy methods are used. The literature data and the description of 2 own clinical observations of the sarcoma from follicular dendritic cells (with the involvement of the maxillary sinus and the nasal cavity) are presented. Treatment (surgery followed by radiotherapy) was successful. The appointment of adjuvant therapy improves the results of treatment in comparison with the surgical method alone.